Enhancing the Pedagogical Competence of Prospective Arabic Teachers through the MBKM Teaching Assistance Program - Zulaikha Nur Khasanah; Muh. Naim Madjid (Journal of Social Work and Science Education, 2026)
The low pedagogical competence of teachers continues to be a significant concern in Indonesian education, particularly in the context of Arabic language instruction. This study explores the role of the MBKM teaching assistance program in fostering pedagogical competence and Pedagogical Content Knowledge (PCK) among prospective Arabic teachers. Using a qualitative systematic literature review, this research examines relevant national and international studies published between 2020 and 2025 to understand how experiential learning in school settings supports teacher development. The results reveal that participation in the MBKM Teaching Assistance program contributes to the enhancement of instructional planning, classroom management, assessment skills, and reflective practices. In addition, the program supports the integration of pedagogical approaches with subject-specific knowledge, which is essential for addressing the structural and linguistic complexities of Arabic. Nevertheless, the success of the program is shaped by factors such as mentoring effectiveness, coordination between institutions, and the initial pedagogical preparedness of participants. This study concludes that the MBKM teaching assistance program offers a promising framework for strengthening pedagogical competence and PCK in Arabic teacher education, particularly when accompanied by systematic mentoring and continuous evaluation.